Leveraging lean in medical laboratories : creating a cost effective, standardized, high quality, patient-focused operation /: creating a cost effective, standardized, high quality, patient-focused operation. (2015) - Protzman, Charles; Kerpchar, Joyce; Mayzell, George
No abstract available